A fullerene-modified protein - Kurz, A; Halliwell, C; Davis, J; Hill, H; Canters, G (1998)
A surface cysteine-containing redox protein (azurin mutant S118C) has been labelled with a C60-based thiol-selective reagent leading to electrochemical interactions between the fullerene and protein redox centre.